Impact of a New Metro Line in Amsterdam on Ridership, Travel Times, Reliability and Societal Costs and Benefits - Brands, Ties; Dixit, Malvika; Oort, Niels van (European Journal of Transport and Infrastructure Research, 2020)
The north-south metro line in Amsterdam became operational in summer 2018, accompanied by changes to the existing bus, metro, and tram network in the city. In this paper we undertake an ex-post analysis of the transportation impacts of the network change. Using two sets of smart card transactions, of 5-6 weeks each, and corresponding Automatic Vehicle Location (AVL) data, a before-after comparison is made, concerning ridership, travel times, number of transfers, and travel time reliability. The results show a 4% increase in network wide working day ridership and a strong shift from tram and bus to metro. On an average working day, more than 6,000 hours of travel time is saved. 21% of travellers have more than 1 minute shorter travel time and 13% of travellers have more than 1 minute travel time increase. Furthermore, slightly fewer transfers are made, and the aggregated effect on travel time reliability is marginally positive. For an average working day (7am to 7pm), the resulting daily societal benefits of the new public transport network are approximately €54,200. On a yearly basis the transport related societal benefits are approximately 22 million euros. Doing an ex-post analysis is not common in the literature and in practice, and therefore in a lot of cases the realized benefits of large infrastructural investments remain unknown. This study provides an example of scientific methodology development using multiple data sources, that enables such ex-post evaluations, leading to improvements in public transport assessment and planning.